Implementasi Metode Circle Time Dalam Pembelajaran Bahasa Arab di Lembaga Bahasa Seblak Jombang - Siti Azura; Adam Al barqi; Syuhadak; Nuril Mufidah (Shaut al Arabiyyah, 2023)
This study aims to determine the implementation of the Circle Time learning method in learning Arabic. The research method used is qualitative with the type of case study. Research data were collected through observation, interviews, and documentation. Data were analyzed by condensation, data display, and verification. The results showed that 1) The implementation of the Circle Time learning method in Arabic learning was carried out in several stages, namely planning, implementation (provocation, discussion, role play, and reflection), and evaluation. 2) The Circle Time learning method can foster students' confidence in speaking using Arabic. 3) The supporting factors for implementing the Circle Time learning method are the flexibility of learning and the teacher's open-mindedness, while the inhibiting factors are time constraints and students who are difficult to condition. It is hoped that this research can be a new reference for Arabic language teachers in choosing learning methods.